MAKNA KESUBURAN DALAM PERTUNJUKAN TAYUB - Rabimin Rabimin (Institut Seni Indonesia Surakarta, 2010)
This article gives the information on the meaning of fertility in Tayub performance in Java which is lately thought to be more negative (Iekoh) than positive. Ironically, many Tayub performances are prohibited in certain regions such as Kecamatan Sambung Macan (Sragen), Kabupaten Gunung Kidul, Special Distric of Yogyakarta and so on.Tayub as the pride of rural people is one of the supreme art supporting the life and preservation of national culture especially Java. One of thefunctions of ritual Tayub is believed as the symbol of fertility for plants and for the soil of rural peasants, and for the people themselves. This article describes a variety of data in Tayub performance, some pros and cons and the explanations. The two opinions have been explained in depth in this article and it can be concluded that the fertility in Tayub can have an effect on the fertility of plants, soil and people (the dancers and audience). This can happen because there are the same elements, namely, the soil essence of vicious passion (Iauwamah), the water essence of sufiah passion supported by the atmosphere (wind) essence of mutmainah (strong drive to avoidimmoral actions) and the fire essence of anger. Those passions are very useful as the foundation of peace if one can handle them.Key words: Tayub, fertility, and meaning